“Sentinel Oculomotor Nerve Palsy”: A Harbinger of Subarachnoid Hemorrhage - Vijay Renga (Case Reports in Neurological Medicine)
Subarachnoid hemorrhage (SAH) is a life-threatening condition most commonly caused by aneurysmal rupture. Sentinel headaches, often described as the “worst headache of life” or a “thunderclap headache,” are critical warning signs that may precede SAH. However, atypical headaches can complicate early diagnosis. Oculomotor nerve palsy, though rare, may occur as a complication of both aneurysmal and nonaneurysmal SAH. We report a unique case of a 64-year-old woman who initially presented with atypical headache followed by isolated oculomotor nerve palsy, preceding the onset of a nonaneurysmal SAH. This case highlights isolated oculomotor palsy as a potential unrecognized sentinel sign of SAH.